Genetic diversity of two tropical tree species of the Dipterocarpaceae following logging and restoration in Borneo: high genetic diversity in plots with high species diversity - Ang, Cheng Choon; O'Brien, Michael J; Ng, Kevin Kit Siong; Lee, Ping Chin; Hector, Andy; Schmid, Bernhard; Shimizu, Kentaro K (Taylor and Francis, 2016)
Background: The impact of logging and restoration on species diversity has been well studied in tropical forests. However, little is known about their effects on genetic diversity within species.